Overview of the First 500 Cardiac Surgeries Performed at Peshawar Institute of Cardiology, Peshawar, Pakistan - Syed Shahkar Ahmed Shah, Abdul Nasir, Muhammad Tariq, Mubashir Zareen Khan, Muhammad Bilal, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To examine the postoperative outcome of the first 500 cardiac surgeries performed at the newly established cardiac institute in Peshawar, Pakistan. Material and methods:This retrospective observational study examines the first 500 cases of cardiac surgery conducted at Peshawar Institute of Cardiology in Peshawar, Pakistan, between December 2020 and October 2021. Off-pump coronary artery bypass (OPCAB), on-pump coronary artery bypass (ONCAB), mitral valve replacement (MVR), aortic valve replacement (AVR), Conventional Ventricular Septal Defect closure (VSD), and congenital procedures were performed by PIC expert faculty. Results:The mean age of the patients was 51.56±17.03 years. There were 371 (74%) males and 129 (25.8%) females. EuroSCORE II recorded was 1.88±0.76. 308 (61.6%) patients presented with Triple-vessel coronary artery disease, followed by Severe symptomatic aortic regurgitation 43 (8.6%). Total 337 coronary artery bypass grafting (CABG) surgeries were performed. 303 ONCAB and 34 OPCAB surgeries. In-hospital mortality was observed in 9 (1.8%), and 17 (3.4%) patients who had postoperative surgical bleeding. The mean ventilation time recorded was 5.66±1.7 hours. The mean hospital recorded was 4.93±1.4 hours Conclusion:Establishing a high-quality cardiac institute in Peshawar has resulted in remarkable outcomes in terms of management and surgical treatment of cardiac diseases.